n = 1 ∑ 2 0 1 5 ( n + 2 ) ( n + 3 ) ( n + 4 ) n = B A
Find A + B where A , B are positive coprime integers.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Simple standard approach once you realize the telescoping series.
Exactly Same Way, had some problem in the end while calculating the sum of those fractions but eventually got the answer. Sir do u have any short method of calculating the sum of such large fractions?
Log in to reply
I use Excel spreadsheet to find out the LCM as denominator then find the nominator.
Hey actual method is of Satvik Pandey not yours .Where you got 1/n+2,1/n+3 and -2/n+4.You are either skipping steps or doing a Hit and trial method.I request you to further add the beggining steps in your solution.Thanks.
This can be written as
2 1 ∑ n = 1 2 0 1 5 ( n + 2 ) ( n + 3 ) ( n + 4 ) 2 n + 4 − 4
2 1 ( ∑ n = 1 2 0 1 5 ( n + 2 ) ( n + 3 ) ( n + 4 ) 2 ( n + 2 ) − 2 1 ( n + 2 ) ( n + 3 ) ( n + 4 ) 4 + ( n + 4 ) − ( n + 2 ) )
∑ n = 1 2 0 1 5 ( ( n + 3 ) 1 − ( n + 4 ) 1 ) − ∑ n = 1 2 0 1 5 ( ( n + 2 ) ( n + 3 ) 1 − ( n + 3 ) ( n + 4 ) 1 )
So, have expressed the sum as difference of consecutive terms. All the intermediate terms get cancelled and only first and last terms are left.
So the answer is 6 1 − 2 0 1 8 × 2 0 1 9 2 0 1 7 . On simplifying we get A + B = 7 9 1 8 9 7
Problem Loading...
Note Loading...
Set Loading...
n + 2 1 + n + 3 1 − n + 4 2 ⇒ ( n + 2 ) ( n + 3 ) ( n + 4 ) 3 n ( n + 2 ) ( n + 3 ) ( n + 4 ) n ⇒ n = 1 ∑ 2 0 1 5 ( n + 2 ) ( n + 3 ) ( n + 4 ) n ⇒ A + B = ( n + 2 ) ( n + 3 ) ( n + 4 ) 3 n + 8 = n + 2 1 + n + 3 1 − n + 4 2 − ( n + 2 ) ( n + 3 ) ( n + 4 ) 8 = n + 2 1 + n + 3 1 − n + 4 2 − 4 ( n + 2 1 − n + 3 2 + n + 4 1 ) = − n + 2 3 + n + 3 9 − n + 4 6 = − n + 2 1 + n + 3 3 − n + 4 2 = n = 1 ∑ 2 0 1 5 ( − n + 2 1 + n + 3 3 − n + 4 2 ) = − n = 3 ∑ 2 0 1 7 n 1 + n = 4 ∑ 2 0 1 8 n 1 + 2 n = 4 ∑ 2 0 1 8 n 1 − 2 n = 5 ∑ 2 0 1 9 n 1 = − 3 1 + 2 0 1 8 1 + 4 2 − 2 0 1 9 2 = 6 7 9 0 5 7 1 1 2 8 4 0 = 1 1 2 8 4 0 + 6 7 9 0 5 7 = 7 9 1 8 9 7